Generating Bacterial Foods in Toxicology Studies with Caenorhabditis elegans. Issue 1 (21st May 2020) - Ke, Tao; Santamaría, Abel; Tinkov, Alexey A.; Bornhorst, Julia; Aschner, Michael
Abstract: Caenorhabditis elegans is a free‐living animal that is used as a powerful experimental model in biological sciences. The natural habitat of the animal are areas rich in material from rotting plants or fruits being decomposed by a growing number of microorganisms. The ecology of the natural habitat of C. elegans is a complex interactive network involving many species, including numerous types of bacteria, viruses, fungi, slugs, snails, and isopods, among which bacteria play multifaceted roles in the natural history of C. elegans . Under laboratory conditions, C. elegans is routinely cultured in a petri dish filled with solidified agar and seeded with Escherichia coli strain OP50, the latter offering an alternative model to study the interaction between bacteria and host. Because of the clear advantages of generating specific bacterial foods for mechanistic studies in C. elegans, it is important to develop a robust protocol to generate high‐quality bacterial foods commensurate with experimental requirements. Based on previous work by us and others, herein we present a protocol on how to generate these optimal bacterial food–based research tools. © 2020 by John Wiley & Sons, Inc. Basic Protocol 1 : Preparing concentrated E. coli OP50 Basic Protocol 2 : Titrating bacteria concentration Basic Protocol 3 : Generating dead bacterial food by heating Basic Protocol 4 : Generating dead bacterial food by antibiotics Basic Protocol 5 : Feeding C. elegans with bacterial foods in liquid